Abnormally high risk of stroke in Brugada syndrome. Issue 2 (February 2019) - de Asmundis, Carlo; Mugnai, Giacomo; Chierchia, Gian-Battista; Sieira, Juan; Ströker, Erwin; Conte, Giulio; Rodriguez-Mañero, Moises; Pappaert, Gudrun; Van Dooren, Sonia; De Regibus, Valentina; La Meir, Mark; Brugada, Pedro
Abstract : Background: The present study sought to evaluate the incidence of cerebrovascular events in a large cohort of patients with Brugada syndrome (BrS) analysing possible predictors, clinical characteristics and prognosis of cardioembolic events secondary to atrial fibrillation. Methods: A total of 671 consecutive patients (age 42.1 ± 17.0 years; men 63%) with a diagnosis of BrS were retrospectively analysed over a mean follow-up period of 10.8 ± 5.5 years. The diagnosis of ischemic stroke was made according to the AHA/ASA guidelines using computed tomography (CT) and angio-CT in the emergency department. Results: Among 671 patients with BrS, 79 (11.8%) had atrial fibrillation. The incidence of cardioembolic stroke in patients with BrS and atrial fibrillation was 13.9% (11 events). These patients had a low CHA2 DS2 Vasc score (82%, 0 and 1). Patients with transient ischemic attack/stroke were more frequently asymptomatic (91 vs. 25%; P  < 0.0001) and older (59.4 ± 11.2 vs. 43.9 ± 16.7; P  = 0.004) as compared with those without cerebrovascular events. Conclusion: The incidence of cardioembolic stroke in patients with BrS and atrial fibrillation was unexpectedly high. The cerebrovascular accidents were often the presenting clinical manifestation and were significantly associated with asymptomatic atrial fibrillation and older age. CHADS2 and CHA2 DS2 Vasc scores did not predict the unexpectedly high risk of thromboembolic events in this group of patients. The use of more invasive diagnostic tools might be useful in order to increase the rate of atrial fibrillation detection.